Procurement Systems Audit and Performance of Devolved Units in Kisii County, Kenya - Osuto, Abraham Mong’eri; Juma, Dennis (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study examined the influence of procurement systems audit on procurement performance in devolved units in Kisii County. The specific objectives were to assess the effect of procurement audit planning, compliance auditing, internal control assessment, and procurement audit reporting on procurement performance. Methodology: A descriptive research design was adopted, and data were collected using structured questionnaires administered to procurement officers, auditors, and finance staff in selected departments within the county. A sample of 60 respondents was selected using stratified and simple random sampling techniques. Data were analyzed using both descriptive and inferential statistics, including Pearson correlation and multiple linear regression. Findings: The findings revealed that all four procurement audit dimensions audit planning, compliance auditing, internal control assessment, and audit reporting had a positive and statistically significant influence on procurement performance. The regression model showed a strong explanatory power, with an R Square value of 0.705, indicating that 70.5% of the variation in procurement performance could be explained by the audit variables. Unique Contribution to Theory Practice and Policy: The study recommended that devolved units invest in risk-based audit planning, strengthen compliance monitoring, improve internal controls, and ensure timely audit reporting and follow-up. Further research is suggested to explore technological innovations in procurement audits and to expand the scope to other counties for broader generalization.